PERSEPSI SIKAP PEDAGANG DAN MASYARAKAT MENGENAI KONDISI LINGKUNGAN PASAR TERHADAP REVITALISASI PASAR DUPA KENCANA PEKANBARU - Denny Mulianto; Aras Mulyadi; Yusni Ikhwan Siregar (Jurnal Ilmu Lingkungan, 2013)
A Study on the public perception and the attitudes asa well as market retailer toward themarked environment condition of Pasar Dupa Kencana Pekanbaru were carred out. Theobjective of the study was to find out. Public perception and willingness in revitalization ofthe market. Total sample of 130 respondens were taken in study. Data Analysis were done byapplying multiple descriptive regression revealed that public opinion on the market conditionwas negative and showed a suggestion to market revitalization. Contrary to public the localtrader argue about the market revitalization. Base on multiple reggresion test, the perceptionand attitude of the public and the trader showed a significant effect on the revitalization ofthe market in addition, where was a significant different between public and trader opinionand intention on the market the revitalization of the market.